sqrt(x^2 +5) = 2x-3

Let us square both sides:

==> [sqrt(x^2+5)]^2 = (2x-3)^2

==> x^2 +5 = 4x^2 - 12x +9

Now group similar:

==> 3x^2-12x +4 = 0

==> x1= [12 + sqrt(144- 4*3*4)]/6= [12 + sqrt96]6 = [12+9.8]/6= 3.63

==> x2= [12- sqrt96]6 = 0.37

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now